Fundamentals of athletic training - Cartwright, Lorin 1956- MS, ATC, CAA; Peer, Kimberly S. EdD (Human Kinetics, 2019)
Fundamentals of athletic training, fourth edition, offers a well-rounded introduction to the field of athletic training. It presents injuries and illnesses commonly encountered by certified athletic trainers and also reviews professional and administrative aspects of the profession. Written specifically for high school and community college students, this text provides foundational knowledge and skills as well as the opportunity for students to evaluate the possibility of a career as a sports medicine professional. The fourth edition presents the latest developments in athletic training with regard to treatment, care, administration, and certification. New material in this edition includes the following: professional preparation and career potential; documentation, record keeping, and electronic injury tracking systems; development and design of an athletic training facility; fiscal management and equipment ordering; analysis of preexisting conditions and preparticipation exams; basic diagnostic tests, including x-rays, ultrasounds, and drug screening tests; ethics for sports medicine professionals. The fourth edition also features a web resource that includes 28 practical skills worksheets and a semester-long project that develops with each chapter to give students a true understanding of the requirements needed to be an effective athletic trainer.